Peptide Analysis from Soil Actinomycetes Exhibiting Antimicrobial and Antiproliferative Activities - Kalyani, Manjula Ishwara (International Journal of Pharmaceutical & Biological Archive, 2018)
Actinomycetes are considered a potential group of microorganisms capable of producing bioactive molecules. In the present study, the actinomycetes species belonging to the genus Thermoactinomycetes, Micromonospora and predominantly Streptomyces were isolated from maize rhizosphere soil and from compost soil. With anticipating the isolation of potential antimicrobial peptides from the actinomycetes isolates, the isolates were subjected for total protein extraction after growing them in starch casein nitrate media. The antimicrobial peptides are low molecular weight peptides attacking the cell membrane by ionic interactions, thus disrupting membrane integrity of invading pathogens or the abnormal cells such as cancer cells. The peptides obtained from actinomycetes were analyzed by SDS-PAGE technique after their salt precipitation and dialysis. The total peptides were checked for antimicrobial activity against the bacteria Pseudomonas sp, Enterobacter sp, Klebsiella sp, Streptococcus sp, Escherichia coli and Staphylococcus aureus. The peptides obtained from Streptomyces predominantly showed effective antibacterial activities. The compost isolated actinomycetes mainly identified belonging to Thermoactinomycetes, Micromonospora and Streptomyces also showed antibacterial activity but showed good antiproliferative effect against the proliferative yeast cultured cell lines. The morphological features of actinomycetes were characterized by gram staining, acid fast staining and slide culture techniques.